DETERMINAN FRAUD HEXAGON THEORY TERHADAP FRAUDULENT FINANCIAL STATEMENT: PENDEKATAN BENEISH M-SCORE MODIFIKASI - Lailatun Usri Noriyah; Alif Faruqi Febri Yanto (Jurnal Proaksi, 2025)
Main Purpose - The purpose of this study was to determine the impact of fraud hexagon theory on Fraudulent Financial Statements (FFS), as measured by the modified Beneish M-Score in the Indonesian mining sector. Method -The purposive sampling technique was used in determining the sample, 92 units of analysis were obtained from the research population which included 58 mining companies listed on the Indonesia Stock Exchange during the period 2020-2023. This research data was analyzed through a logistic regression model. Main Findings - The results of the analysis reveal that only capability (change of directors) has an impact on FFS. Other factors, such as stimulus, opportunity, rationalization, ego, and collusion are not proven to have an impact on FFS. Change of directors is more common in companies detected as manipulators. Theory and Practical Implications - The implications of the study emphasize the importance of close supervision of individuals in strategic positions, especially those with high capabilities such as directors, because their abilities have been proven to be a driver of FFS. This research can assist auditors, shareholders and other stakeholders in identifying and detecting Fraudulent Financial Statement. Novelty - This study uses the modified Beneish M-Score in measuring FFS, so that the research results are more relevant to Indonesia in the current era.